EVOLUTIONARY ANALYSIS OF POLLINARIA MORPHOLOGY OF SUBTRIBE AERIDINAE (ORCHIDACEAE) - Topik Hidayat (Research Center for Biology, 2006)
HIDAYAT, TOPIK; YUKAWA, TOMOHISA; ITO, MOTOMI. 2006. Evolutionary analysis of pollinaria morphology of subtribe Aeridinae (Orchidaceae). Reinwardtia 12(3): 223–235.–– Pollinarium is one of the distinct synapomorphies of Orchidaceae. With using characters derived from the pollinarium, phylogenetic relationships among genera of subtribe Aeridinae was examined. Cladistic analysis showed that (1) Subtribe Aeridinae is monophyletic group. (2) Five of six groups constructed in the analysis are consistent with the groups recognized in previous molecular phylogenetic analyses.(3)The genera Cleisostoma and Phalaenopsis are non-monophyletic group.(4) Pollinarium morphology endorses monophyly Trichoglottis and Phalaenopsis alliances. (5) Although transformation of the stipe and viscidium shapes in the subtribe is subjected to parallelism, the results showed that these characters are much useful in determining relationships in the subtribe than those of pollinium.